The Growing Accountability Agenda: Progress or Mixed Blessing? - Salmi, Jamil (International Higher Education, 2008)
In the past decade, however, accountability has become a major concern in most parts of the world. Governments, parliaments, and society at large are increasingly asking universities to justify the use of public resources and account more thoroughly for their teaching and research results. The universal push for increased accountability has made the role of university leaders much more demanding. The successful evolution of higher education institutions will hinge on finding an appropriate balance between credible accountability practices and favorable autonomy conditions.